The Paucity of Female Educational Leadership in Politically Volatile Context of Zimbabwe - Zvisinei Moyo (Camarines Sur Polytechnic Colleges, 2024)
Zimbabwe is one country that experienced deep political turmoil soon after attaining independence in 1980. This study explored the intertwining of violent politics, the politics of fieldwork and the paucity of female educational leadership research by examining the volatile contexts within which the process of knowledge construction takes place. The researcher reviewed related literature to gain insights into the impact of volatile context on research. The study provides a review of literature on issues and concepts related to the studies put forward by other scholars within which the study was discussed and analysed. The review of related literature was conducted mainly to analyse three interweaving factors: the visibility of studies on educational leadership and management publications in 2008, migration and political violence in Zimbabwe. The study established that the terror operation (Gukurahundi) waged in Midlands, Matebeleland South and Matebeleland North provinces from 1982 to 1987, the formation of the political opposition party - Movement for Democratic (MDC) and commercial farm invasions in 1999, operation Murambatsvina in 2005 and elections in 2008 are enough evidence that the Mugabe regime developed a tradition of using violence and intolerance as a tool of consolidating political power. These events formed a complex multi-layered volatility that silenced not only academic research but other forms of documentation.